Structure-based identification of bioactive phytochemicals targeting kallikrein-related peptidase 2 for prostate cancer therapy - Jairajpuri, Deeba Shamim; Hussain, Afzal; Alajmi, Mohamed F.; Mohammad, Taj; Shamsi, Anas; Hassan, Md. Imtaiyaz (Frontiers in Chemistry, 2025)
Kallikrein-related peptidase 2 (KLK2) is a serine protease exhibiting antiangiogenic properties through proteolytic activity. KLK2 is overexpressed in prostate cancer and plays a pivotal role in cancer progression, establishing it as a potential therapeutic target. Despite the promising results of small molecule inhibitors targeting KLK2 in prostate cancer treatment, there are still many challenges in the development and application of these inhibitors. As a consequence, very few KLK2 inhibitors have advanced to clinical trials because of issues with specificity and selectivity. Moreover, the precise mechanisms underlying KLK2’s interactions with small molecule inhibitors remain inadequately understood. This study used structure-based virtual screening of a phytochemical library and found three compounds, Phaseolin, Withaphysalin D, and Nicandrenone, as potential KLK2 inhibitors. These compounds exhibited high binding affinities (−8.9 to −8.8 kcal/mol), favorable pharmacokinetic profiles, and stable interactions with KLK2’s catalytic residues (including His65) in docking studies. Their binding was further validated through MM-PBSA free energy calculations, which confirmed energetically favorable interactions with KLK2. The findings suggest that these phytochemicals have a high potential to be exploited as novel KLK2 inhibitors with improved efficacy. While experimental validation of enzymatic inhibition and antitumor efficacy is required, this study provides a structural and mechanistic foundation for advancing these candidates into preclinical testing. These results also highlight the use of phytochemical libraries and dynamics-driven virtual screening in developing targeted therapies for prostate cancer.